Landasan politik dan hukum dalam pendidikan islam - Aulia, Rahma Awalina (Maliki Interdisciplinary Journal, 2025)
Education is a fundamental aspect of national development, particularly in Indonesia with its cultural and religious diversity. This article aims to analyze the concept of Islamic education and its relevance to the national education system. Islamic education is understood as a holistic process of human development derived from the Qur’an and Hadith, oriented toward shaping an ideal person (insan kamil) who is faithful, knowledgeable, and virtuous. The method employed is a literature review by examining normative foundations, historical developments, and educational policies in Indonesia. The findings reveal that Islamic education, from the pre-independence era to the reform period, has played a significant role in integrating pesantren, madrasah, and public schools into the national education framework. Moreover, Islamic education contributes substantially to nation-building through the internalization of spiritual, moral, and social values. The discourse on religious moderation emerges as a crucial strategy to address the challenges of globalization and modernization that influence the direction of education. In conclusion, Islamic education is not merely a complementary element within the national education system but serves as a vital foundation for shaping a generation that is excellent, moderate, and globally competitive.